PERKULIAHAN PERSAMAAN DIFERENSIAL BIASA MENGGUNAKAN COMPUTER AIDED DESIGN UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KEMAMPUAN PEMECAHAN MASALAH MAHASISWA - Sujito, - (2023)
Critical thinking skills have a significant and essential role for students in solving problems to prepare themselves for real-world challenges and academic complexities. Computer-Aided Design (CAD) with Maple software in Ordinary Differential Equations courses improves students' critical thinking and problem-solving abilities. The research method is mixed methods with an embedded experimental model design. A small-scale pilot study at a state university in Bandung involved 42 students, and program implementation at a state university in Malang was divided into control (51 people) and experimental (55 people) groups. Quantitative data collection uses a test instrument integrated with PDB material for critical thinking skills in multiple-choice (11 questions) and problem-solving abilities in the form of essays (4 questions). Qualitative data was collected by observation, attitude scale, and interviews. Data were analyzed quantitatively, qualitatively, and combined analysis. The results showed an increase in students' critical thinking skills in the medium category. The indicator for building basic skills experienced the highest increase and the lowest for the indicator for managing strategy and tactics. In problem-solving abilities, all indicators have increased in the medium category. The highest increase was in the Mathematical procedure indicator, and the lowest was in the useful description. Maple Software positively influences the moderate category (d = 0.70) in facilitating the achievement of critical thinking skills and the medium category (d = 0.68) in problem-solving abilities. The advantage is that learning is done more interactively and can visualize equations, explore lecture topics more deeply, and train students' skills to think more critically in solving problems. The limitation is that students need help determining the variables that affect physical processes when dealing with physical phenomena. The characteristics of lectures are using a problem-based approach, being able to integrate scientific and technological developments in learning, and being able to improve critical thinking skills.